Expression and clinical implications of PARs in the stenotic tissue of ureteropelvic junction obstruction - Wang, Tianyi; Fu, Mingcui; Yan, Xiangming; Song, Hongcheng; Zhang, Weiping (Frontiers in Pediatrics, 2023)
Objective： To explore the expression and clinical implications of protease activated receptors (PARs) in the pathogenesis of children with ureteropelvic junction obstruction (UPJO).Material and methods：Immunohistochemistry was employed to investigate the distribution of PARs in both normal human ureteropelvic junction (UPJ) and cases of UPJO. Furthermore, PAR gene expression levels were assessed using real-time PCR (RT-PCR), and the patients in the UPJO group were stratified according to the Onen grading system. Subsequently, the clinical implications of PARs in UPJO were explored through RT-PCR analysis.Results： Immunofluorescence showed robust PAR2 expression in the control group compared with the UPJO group. The results of RT-PCR analysis revealed a significant decrease in the relative mRNA expression of PAR2 in the UPJO group compared to the control group. Notably, the relative RNA expression of PAR1 was significantly lower in the Onen-4 group compared to the control group. Furthermore, the relative mRNA expression of PAR2 exhibited a statistically significant difference among the Onen-3 group, Onen-4 group, and control group.Conclusions： PARs are widely distributed throughout the SIP syncytium of the UPJ and play a role in maintaining smooth muscle cells (SMCs) membrane potential by interacting with interstitial cells of Cajal (ICCs), as well as platelet-derived growth factor receptor alpha-positive cells (PDGFR α+ cells). The decreased expression of PAR1 suggests a higher preoperative Onen grade in UPJO patients. Furthermore, the downregulation of PAR2 effects at the UPJ may be involved in the loss of inhibitory neuromuscular transmission, disrupting the rhythmic peristalsis of the UPJ.